Rhipicephalus microplus and Ixodes ovatus cystatins in tick blood digestion and evasion of host immune response - Parizi, Luís Fernando; Sabadin, Gabriela Alves; Alzugaray, María Fernanda; Seixas, Adriana; Logullo, Carlos; Konnai, Satoru; Ohashi, Kazuhiko; Masuda, Aoi; da Silva Vaz Jr, Itabajara (Parasites & vectors, 2015)
BACKGROUND: Cystatins are a group of cysteine protease inhibitors responsible for physiological proteolysis regulation and present in a wide range of organisms. Studies about this class of inhibitors in parasites have contributed to clarify their roles in important physiological processes, like blood digestion and modulation of host immune response during blood feeding. Thus, cystatins are a subject of research on the development of new parasite control methods. Additionally, the characterization of proteins shared by different parasite species represents a valuable strategy to find potential targets in multi-species control methods. However, cystatin functions in ticks remain undetermined, especially in Rhipicephalus microplus and Ixodes ovatus, two species that affect livestock and human health, respectively. METHODS: Here we report the inhibitory profile of two R. microplus (BrBmcys2b and BrBmcys2c) and one I. ovatus (JpIocys2a) cystatins to commercial cathepsins B, C, and L. The presence of native cystatins in R. microplus tissues was analyzed using sera against recombinant BrBmcys2b and BrBmcys2c. Also, a peptide from JpIocys2a was synthesized for rabbit immunization, and this serum was used to analyze the cross antigenicity between R. microplus and I. ovatus cystatins. RESULTS: Enzymatic inhibition profile of tick cystatins shows a distinct modulation for cathepsins related to tick blood digestion and evasion of host immune response. Furthermore, BrBmcys2b was detected in saliva and different tissues along tick stages, while BrBmcys2c was detected mainly in gut from partially engorged R. microplus females, demonstrating a distinct pattern of cystatin expression, secretion and traffic between tick tissues. Moreover, phylogenetic analysis suggests that JpIocys2a belongs to the group of tick gut secreted cystatins. Finally, cross-antigenicity assays revealed that antibodies against the JpIocys2a peptide recognize native and recombinant R. microplus cystatins. CONCLUSION: The presence of these proteins in different tissues and their ability to differentially inhibit cathepsins suggest distinct roles for JpIocys2a, BrBmcys2b, and BrBmcys2c in blood digestion, egg and larvae development, and modulation of host immune response in tick physiology. The cross-antigenicity between native and recombinant cystatins supports further experiments using JpIocys2a, BrBmcys2b, and BrBmcys2c as vaccine antigens.